CHRONIC INFLAMMATORY DEMYELINATING POLYRADICULOPATHY - Noer Hassianni Mercy L. Tobing; Agus Yudha Wijaya; Christina Aritonang; Yoyok Hendro (Fakultas Kedokteran, Universitas Palangka Raya, 2021)
Chornic inflammatory demyelinating polyradiculoneuropathy (CIDP) it is an disease of immune-mediated neuropathy (neuropathy due to immunological disorders), rare, the disease that can take many forms (heterogeneous), but treatable,. For much of 20th centuries the introduction of CIDP has been limited so that it is referred to under different disease names. Clinical and histopathologic descriptions are often confused with a disease-like appearance such as Guillain-Barre 'syndrome. To diagnose CIDP, it is necessary to perform an eletromyography (EMG) examination to assess the velocity of nerve conduction and this is an definite diagnostic test. Neural ultrasound and MRI can also help in diagnosis. CIDP is divided into two types, namely typical CIDP and atypical variants of CIDP. Atypical variants of CIDP with different phenotypes present a diagnostic challenge.